Carbon Dioxide Absorption and Release Properties of Pyrolysis Products of Dolomite Calcined in Vacuum Atmosphere - Fei Wang; Toshihiro Kuzuya; Shinji Hirai; Jihua Li; Te Li (The Scientific World Journal)
The decomposition of dolomite into CaO and MgO was performed at 1073 K in vacuum and at 1273 K in an Ar atmosphere. The dolomite calcined in vacuum was found to have a higher specific surface area and a higher micropore volume when compared to the dolomite calcined in the Ar atmosphere. These pyrolysis products of dolomite were reacted with CO2 at 673 K for 21.6 ks. On the absorption of CO2, the formation of CaCO3 was observed. The degree of absorption of the dolomite calcined in vacuum was determined to be above 50%, which was higher than the degree of absorption of the dolomite calcined in the Ar atmosphere. The CO2 absorption and release procedures were repeated three times for the dolomite calcined in vacuum. The specific surface area and micropore volume of calcined dolomite decreased with successive repetitions of the CO2 absorption and release cycles leading to a decrease in the degree of absorption of CO2.